Exploring the Selection of the Optimal Web Service Composition through Ant Colony Optimization - Chifu, Viorica Rozina; Salomie, Ioan; Pop, Cristina Bianca; Niculici, Alexandru Nicolae; Suia, Dumitru Samuel (Computing and Informatics, 2015)
This paper presents an ant-inspired method for selecting the optimal or a near optimal solution in semantic Web service composition. The proposed method adapts and enhances the Ant Colony Optimization meta-heuristic and considers as selection criteria the QoS attributes of the services involved in the composition as well as the semantic similarity between them. To improve the performance of the proposed selection method a 1-OPT heuristic is defined which expands the search space in a controlled way so as to avoid the stagnation on local optimal solutions. The ant-inspired selection method has been evaluated on a set of scenarios having different complexities and comparatively analyzed with a cuckoo-inspired and a bee-inspired selection method.